Draft Annual Plan, 1987-88 Part Two Maharashtra State - Planning Commission (Planning Commission, 1987)
Abstract Statement indicating sub-sector wise outlays and expenditure Statement showing provision for Removal of Regional Backlog Statement indicating scheme wise outlays and expenditure(including outlays for Removal of Backlog) Statement indicating selected physical targets and achievements Statement Indicating outlays and Expenditure in respect of Minimum Needs Programme Statement indicating physical targets and achievements in respect of Minimum Needs Programme Statement indicating outlays and expenditure in respect of Centrally Sponsored Schemes Abstract Statement indicating outlays and expenditure is respect of Tribal Area Sub-Plan Abstract Statement indicating outlays and expenditure in respect of Special Component Plan Abstract Statement of District Plan outlays Statement indicating outlays and expenditure in respect of 20-Point Programme
Maharashtra State